A Política de Atenção à Saúde do Homem no Brasil e os desafios da sua implantação: uma revisão integrativa. - Nogueira Da Silva, Patrick Leonardo; Maciel, Mauro Moreira; Carfesan, Carolina Saiberth; Santos, Silas; Ribeiro De Souza, Jacqueline (Enfermería Global, 2013)
This study aims to identify the challenges for the implementation of the National Policy for Integral Attention to human health. It is an integrative review consisted of searching the databases LILACS, SciELO and BDENF the period between 2000 and 2012. The results initially found 3,738 articles that presented the descriptors Men's Health, Gender and Health and Primary distributed in the databases mentioned. After observing the intersection of descriptors cited articles that present information in context that answer research question of this study were selected fifteen (15) items to be part of this integrative review. Therefore, examine what males look for in a healthcare facility, and from this analysis plan actions in order to meet the health demands that the male population, are measures that can be taken through restructuring in Basic Health Units and the work of professionals who serve the males.